(untitled) - Krishnamurti, J. (London, 1971)
This book has been written at Krishnamurti's suggestion and has his approval. The words have been chosen from a number of his recent talks, taped and previously unpublished, to audiences in various parts of the world.
Keywords: Human beings,Loài người,Self (Philosophy),Tự học (Triết học)